2020
DOI: 10.1111/jcmm.15697
|View full text |Cite
|
Sign up to set email alerts
|

Absent in melanoma 2 enhances anti‐tumour effects of CAIX promotor controlled conditionally replicative adenovirus in renal cancer

Abstract: Conditionally replicative adenoviruses (CRAds) were promising approach for solid tumour treatment, but its oncolytic efficiency and toxicity are still not satisfactory for further clinical application. Here, we developed the CAIX promotor (CAIXpromotor)‐controlled CRAd armed with a tumour suppressor absent in melanoma 2 (AIM2) to enhance its oncolytic potency. The CAIXpromotor‐AIM2 adenoviruses (Ad‐CAIXpromotor‐AIM2) could efficiently express E1A and AIM2 in renal cancer cells. Compared with Ad‐CAIXpromotor, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…The specimens from tissues and cells were lysed by the lysis buffer. The contents of total proteins were evaluated by Bradford method, and a microplate reader was employed to examine the optical density (OD) values at the wavelength of 405 nm, which was utilized to represent caspase‐1 activity according to the previous study 25 …”
Section: Methodsmentioning
confidence: 99%
“…The specimens from tissues and cells were lysed by the lysis buffer. The contents of total proteins were evaluated by Bradford method, and a microplate reader was employed to examine the optical density (OD) values at the wavelength of 405 nm, which was utilized to represent caspase‐1 activity according to the previous study 25 …”
Section: Methodsmentioning
confidence: 99%
“…Notably, Chai and colleagues found that overactivation of AIM2 promotes hepatocellular carcinoma metastasis to inhibit the invasion of renal carcinoma [28], and they subsequently designed H1/pAIM2 nanoparticles to provide a novel therapeutic target for renal carcinoma [29,30]. Recently, they further found that AIM2 exerted significant anti-tumour effects in treatment of renal cancer [31], whereas M1 macrophages activated by AIM2 would foster the rejection of renal carcinoma [32]. Hence, these results provide adequate evidence for the immunological mechanism of AIM2 involvement in renal diseases or cancers.…”
Section: Discussionmentioning
confidence: 99%